Strategies for Managing Facilities and Infrastructure in Islamic Elementary Education: A Qualitative Study of Madrasah Ibtidaiyah Ma’arif Sokorini - Hafuza, Wahyu Nur (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2025)
Purpose – This study aims to examine the actual condition of facilities and infrastructure management and to formulate strategic improvements to enhance its effectiveness at Madrasah Ibtidaiyah Ma’arif Sokorini. Design/methods – The study employed a descriptive qualitative approach, collecting data through in-depth interviews, systematic observations, and document analysis over a three-month period. Data were analyzed using an interactive model involving data condensation, data display, and conclusion drawing, supported by source and method triangulation to ensure credibility. Findings – The findings show that facilities and infrastructure management has been implemented through eight interrelated stages—planning, procurement, storage, distribution, inventory, maintenance, disposal, and supervision—reflecting a comprehensive management framework. However, most processes remain manual, lack written standard operating procedures, and are not supported by integrated digital systems, resulting in weaknesses in documentation, inventory accuracy, maintenance scheduling, supervision, and asset disposal. Research implications/limitations – This study contributes to the theoretical understanding of facilities management by contextualizing general management principles within Islamic elementary education. Nevertheless, its focus on a single madrasah and reliance on qualitative data limit the generalizability of the findings, indicating the need for broader comparative and mixed-method research in future studies. Practical implications – The results suggest that madrasah leaders and policymakers should prioritize the development of written SOPs, digital inventory and financial management systems, structured maintenance plans, and performance-based supervision mechanisms to improve transparency, accountability, and institutional efficiency. Originality/value – This study offers empirical insights into facilities and infrastructure management practices in an Islamic elementary school context, bridging normative management theory with real-world implementation and providing a contextual reference for strengthening educational quality and sustainability in madrasah institutions.